Mapping the landscape of avatar marketing: a bibliometric analysis of trends and future directions - Andriani Kusumawati; Sartika; Anni Rahimah; Yusri Abdillah (Cogent Business & Management, 2024)
This research aims to synthesize a contemporary understanding of avatar marketing by employing advanced bibliometric analysis and data visualization techniques. It addresses existing gaps in the literature and delineates a clear path for future research. By systematically reviewing 185 research publications from the Scopus database, spanning 2004 to 2024, the study evaluates global trends in research output, identifying key contributors such as authors, journals, countries, and leading institutions. Utilizing Biblioshiny and VOSviewer, the analysis uncovers emerging patterns, thematic evolutions, and collaboration networks within the field. Findings highlight the geographical distribution of research activities and the development of new subfields over time. The study provides a detailed map of the current state of avatar marketing research, suggesting areas for further exploration, including interdisciplinary studies and examining cultural differences. This comprehensive review offers valuable insights and a robust framework for future research, contributing significantly to the field by enhancing our understanding and proposing a trajectory for future investigations.
Keywords: 650; Avatar marketing; avatars; bibliometric analysis; marketing; VOSviewer; Biblioshiny